Etika Kebajikan Aristoteles dan Pendidikan Akuntansi dalam Menyusun Laporan Keuangan Perusahaan : Literature Review - Hopong, Yoanelita Maria; Sudaryati, Erina (Owner : Riset dan Jurnal Akuntansi, 2024)
This research explores the benefits of applying Aristotle's virtue ethics and accounting education to preparing company financial reports. The methodology used is a systematic literature review (SLR) with a narrative synthesis approach. The literature search process was conducted using three combinations of keywords: “virtue ethics AND accounting education,” “virtue ethics AND finance report,” “virtue AND financial report,” and “virtue AND finance.” From this search, 13 relevant articles were found, consisting of 1 article from the Elsevier journal, 2 from the Emerald journal, 4 from the ProQuest journal, 5 from the SpringerLink journal, and 1 from the Ebsco journal. Research findings show that implementing virtue ethics in companies can motivate accountants to act with integrity and without fear. However, there is a view that not all accountants find this approach profitable or relevant, especially when viewed from the perspective of short-term profits. In addition, effective accounting education must emphasize two main aspects: technical expertise and moral expertise. The integration of these two aspects is important to ensure that financial reporting standards prepare financial reports and adhere to high ethical standards. This research also found that literature on virtue ethics in the accounting context is still rare and geographically uneven. This indicates the need for further research to understand how Aristotle's virtue ethics and accounting education can be effectively applied in the practice of preparing financial reports for companies.